Keanekaragaman dan Kelimpahan Kumbang Kulit Kayu (Curculionidae: Scolytinae) di Hutan Pendidikan Gunung Walat, Jawa Barat - Andi Dewi Rizka Ainulia M; Muh Rizaldi Trias Jaya Putra (Universitas Hasanuddin, 2020)
Bark beetles (Curculionidae: Scolytinae) has important role in the ecosystem, mainly as decomposer. In this research, we studied the diversity and abundance of bark beetles in Gunung Walat Education Forest at Sukabumi, West Java. This area located at an altitude of 500-700m asl with about 349 ha. Bark beetles were collected by pitfall traps in four types of habitat, i.e., agathis forest, pine forest, schima forest, and mixed forest. A total of 11145 individuals belong to 11 species of bark beetles were found, i.e., Poecilips variabilis, Thamnurgides sp., Cryphalus sp1., Cryphalus sp2., Xyleborus morstatti, X. propecaniclatus, X. morigerus, X. nepotulo, X. masearemsis, Xyleborus sp1, and Xyleborus sp2. Highest abundance of bark beetle was found in the schima forest (4175 individuals) and the lowest was found in pine forest (1548 individuals). Diversity of bark beetle was highest in Schima forest (H= 0,36, E= 0,26) and the lowest in Pine forest (H'= 0,27, E= 0,19). The evenness value of bark beetle in four habitat type is very low (E= 0,19 – 0,26). There are two species dominant of bark beetles, i.e P. variabilis and Thamnurgides sp. The highest number of individual bark beetles was found in Schima forest (4175 individuals; 37%) and the lowest in Pine forest (1548 individuals; 14%). The species number of bark beetles was highest in mixed forest (seven species; 41%).